Evaluation of Traffic Space Occupancy Levels Due To Illegal Parking in Urban Commercial Areas - Mira Lestira Hariani; Martinus Agus Sugiyanto; Abdullah Fatah; Ryan Abdurahman; Sari Kurniasih (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Illegal parking in urban commercial corridors is commonly treated as a public-order problem. From a spatial perspective, however, it also reflects a shift in roadway function, where traffic space is temporarily converted into static space. This study examines that shift using longitudinal occupation (OL), effective width reduction (EWR), and a proposed composite measurement approach termed the Space Pressure Index (SPI). The case site is an approximately 200 m urban commercial segment where vehicles routinely park in parallel on both sides despite the absence of formal parking facilities. Data were collected through a four-day parking patrol survey covering two weekdays and two weekend days, supported by roadway-width measurements under two-sided parking conditions. The results show a clear time-dependent pattern: parking builds up and intensifies during peak commercial hours. Longitudinal occupation peaked at 120.7%, meaning that the cumulative equivalent length of parked vehicles exceeded the usable segment length during the busiest period. At the same time, two-sided parking reduced the effective width by 36.7% relative to the initial geometric width. When these two dimensions are combined, the SPI reached a maximum of 44.3%, indicating substantial functional conversion of movement space during the peak interval. Overall, the findings frame illegal parking in commercial areas as a measurable form of space competition with direct operational implications for corridor mobility. Compared with partial occupancy measures, the proposed OL-EWR-SPI approach offers a clearer segment-scale description of how roadway space is reallocated over time.